Environmental Kuznets Curve in Bulgaria - Georgi Kalchev (International Conference on Interdisciplinary Social Science Studies ICISSS 2016 (Oxford) Conference Proceedings, 2016)
This paper carries out an empirical test of the Environmental Kuznets Curve hypothesis with Bulgarian data on pollution and GDP per capita for the years 1970-2008. The existence of such a curve is confirmed in most cases.
Keywords: 330; Environmental Kuznest Curve; pollution